EVALUATION OF ANTIMICROBIAL ACTIVITIES OF ENDOPHYTIC MICROORGANISMS AGAINST MAJOR PATHOGENS OF CITRUS (Journal of Plant Disease Sciences, 2025)
The present study was conducted to evaluate the antagonistic activity of selected endophytic microorganisms against major plant pathogens. The experiment was carried out at the AICRP on Fruits scheme laboratory and the Department of Plant Pathology, Post Graduate Institute, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola. A total of seven endophytic microorganisms were isolated from healthy and asymptomatic leaves of Nagpur mandarin (Citrus reticulata). These included fungal endophytes, namely Colletotrichum siamense, Diaporthe miriciae, Colletotrichum gigasporum, Aspergillus oerlinghausenensis, Lasiodiplodia curvata, Aspergillus fumigatus, and one bacterial endophyte, Pseudomonas fluorescens. The antimicrobial potential of these endophytes was assessed in vitro using dual culture assays against major citrus pathogens, viz., Fusarium solani, Xanthomonas citri pv. citri, and Pantoea ananatis. Among the tested isolates, Pseudomonas fluorescens exhibited the strongest antagonistic activity, significantly suppressing the mycelial growth of Fusarium solani and Xanthomonas citri pv. citri. In addition, the fungal endophyte Aspergillus fumigatus effectively inhibited the growth of Fusarium solani and Xanthomonas citri pv. citri. The results indicate the potential of selected endophytes, particularly Pseudomonas fluorescens, as effective biological control agents against important citrus pathogens.
Keywords: Antagonistic activities, Citrus reticulata, Dual culture, Endophytes, Pseudomonas fluorescens